2003
DOI: 10.2320/matertrans.44.2541
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Martensitic Transformation of γ-FeN in a Magnetic Field

Abstract: Isothermal martensitic transformation of the -FeN was found to occur in magnetic field at temperatures above the Ms. Molar fraction of martensite monotonically increases with increasing isothermal aging time, and saturates at a value proportional to applied magnetic field. Temperature and magnetic field dependence of the saturation value indicates that the transformation does not proceed above the temperature where the value become zero in a given magnetic field. Application of magnetic field reveals intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A magnetic field of such a strength can affect the transformation temperature and microstructure to a readily visible extent if the transformed phase is either ferromagnetic or has a substantially different susceptibility from the parent phase. Under this circumstance studies of magnetic field effects are expanded to other alloys and phase transformations [15][16][17][18][19][20]. In particular, the effects on diffusional transformations in ferrous alloys have attracted considerable attention for a few decades.…”
Section: Introductionmentioning
confidence: 98%
“…A magnetic field of such a strength can affect the transformation temperature and microstructure to a readily visible extent if the transformed phase is either ferromagnetic or has a substantially different susceptibility from the parent phase. Under this circumstance studies of magnetic field effects are expanded to other alloys and phase transformations [15][16][17][18][19][20]. In particular, the effects on diffusional transformations in ferrous alloys have attracted considerable attention for a few decades.…”
Section: Introductionmentioning
confidence: 98%
“…48,50 Martensite formation was investigated by magnetometry, which has been demonstrated to be an accurate technique to study the martensitic transformation in iron based alloys. 44,45,49,[51][52][53][54][55] Magnetometry was supplemented by electron backscatter diffraction, 56 which was applied to evaluate the morphology of martensite.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Koyano 35,36) studied the formation of 0 Fe 16 N 2 from Fe-N austenite in an attempt to fabricate a bulk single crystal of 0 Fe 16 N 2 . They observed that to 0 martensitic transformation occurred isothermally at liquid helium temperature, which was above M s in a field of less than 40 T. …”
Section: Martensitic Transformationmentioning
confidence: 99%